Path diagram of SEM-PLS Public Perception of Ecotourism in Jambi Province - Mardhotillah, Bunga; Mubarak, Fadhlul; Sundara, Vinny Yuliani; Yanova, Shally; Gusmanely Z, Gusmanely Z (Global Education Journal, 2025)
Tourism activities are a necessity for individuals and communities because they provide a refreshing impact, both physically and spiritually. One tourism activity that can bring humans closer to nature and the Creator is ecotourism or ecological tourism. This study aims to analyze the factors influencing public perceptions and preferences in Jambi Province towards Ecological Tourism during the Covid-19 Pandemic, spanning the initial pandemic period, PSBB, PPKM, New Normal, and post-pandemic. This research method uses a quantitative approach with primary data from a survey in the form of questionnaires distributed to the community, which data analysis uses SEM-PLS assisted by Smart-PLS software. The results of this study suggest that based on the SEM-PLS path diagram, the path coefficients indicate that all aspects of visitor assessments of ecological tourism destinations in Jambi Province need to be improved, especially related to tourist destination cleanliness, ecological tourism accessibility, tourist attractions, and infrastructure conditions. Therefore, good cooperation between the community and the government is highly recommended in the management of ecological tourism areas in Jambi Province.